The Influence of Design for Manufacturing and Assembly on Production Efficiency and Product Quality; A Case Study of a 0.5 Inch Class 800LB Ball Valve - Muhammad Nur Apriady; Bambang Syairudin (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The manufacturing industry faces increasing pressure to enhance production efficiency while maintaining high product quality standards. Design for Manufacturing and Assembly (DFMA) has emerged as a critical methodology for addressing these challenges by integrating manufacturing and assembly considerations into the early design phase Objective: This study aims to analyze the effect of implementing the Design for Manufacturing and Assembly (DFMA) approach on production efficiency and product quality in the manufacturing of a 0.5-inch Class 800LB Ball Valve. Methods: The research adopts a quantitative approach with a comparative analysis between the initial design and the optimized design developed based on DFMA principles. Data were collected through direct observation of manufacturing and assembly processes, in-depth interviews with production engineers, and examination of technical documentation regarding process time, cost structure, and component quantity. Results: The results show that applying DFMA significantly reduces assembly time by approximately 20%, decreases the number of non-value-added components, and simplifies the assembly sequence, which collectively enhance overall production efficiency. Furthermore, the redesigned product demonstrates improved quality consistency, lower assembly defect rates, and better structural reliability during performance testing. Integrating DFMA with Value Analysis and Value Engineering (VAVE) also contributes to a more cost-effective and sustainable manufacturing system by aligning design simplicity with functional performance. Conclusion: The findings emphasize that DFMA is not only a tool for operational improvement but also a strategic design framework that supports competitiveness, lean production, and continuous improvement in industrial environments. Hence, DFMA implementation is recommended as a standardized design practice to achieve efficiency, quality assurance, and innovation within the manufacturing sector.